High-resolution geochemical record of fluid–rock interaction in a mid-crustal shear zone: a comparative study of major element and oxygen isotope transport in garnet - Raimondo, T; Clark, Chris; Hand, Martin; Cliff, John; Harris, C (Blackwell Publishing, 2012)
Garnet grains from an intensely metasomatized mid-crustal shear zone in the Reynolds Range, central Australia, exhibit a diverse assortment of textural and compositional characteristics that provide important insights into the geochemical effects of fluid–rock interaction. Electron microprobe X-ray maps and major element profiles, in situ secondary ion mass spectrometry oxygen isotope analyses, and U–Pb and Sm–Nd geochronology are used to reconstruct their thermal, temporal and fluid evolution. These techniques reveal a detailed sequence of garnet growth, re-equilibration and dissolution during intracontinental reworking associated with the Ordovician–Carboniferous (450–300 Ma) Alice Springs Orogeny. A euhedral garnet porphyroblast displays bell-shaped major element profiles diagnostic of prograde growth zoning during shear zone burial. Coexisting granulitic garnet porphyroclasts inherited from precursor wall rocks show extensive cation re-equilibration assisted by fracturing and fragmentation. Oxygen isotope variations in the former are inversely correlated with the molar proportion of grossular, suggesting that isotopic fractionation is linked to Ca substitution. The latter generally show close correspondence to the isotopic composition of their precursor, indicating slow intergranular diffusion of O relative to Fe2+, Mg and Mn.Peak metamorphism associated with shearing (~550 °C; 5.0–6.5 kbar) occurred at c. 360 Ma, followed by rapid exhumation and cooling. Progressive Mn enrichment in rim domains indicates that the retrograde evolution caused partial garnet dissolution. Accompanying intra-mineral porosity production then stimulated limited oxygen isotope exchange between relict granulitic garnet grains and adjacent metasomatic biotite, resulting in increased garnet δ18O values over length scales <200 μm. Spatially restricted oxygen interdiffusion was thus facilitated by increased fluid access to reaction interfaces. The concentration of Ca in channelled fracture networks suggests that its mobility was enhanced by a similar mechanism. In contrast, the intergranular diffusion of Fe2+, Mg and Mn was rock-wide under the same P–T regime, as demonstrated by a lack of local spatial variations in the re-equilibration of these components. The extraction of detailed reaction histories from garnet must therefore take into account the variable length- and time-scales of elemental and isotopic exchange, particularly where the involvement of a fluid phase enhances the possibility of measureable resetting profiles being generated for slowly diffusing components such as Ca and O, even at low ambient temperatures and relatively fast cooling rates.